The mesoeconomy of the "DONA”, a new approach to the development of productive cluster (Costos y Gestión, 2022)
In 2008, in the midst of the global crisis, I proposed a “Complex Dashboard for a productive agglomerate in the meso economy”. Time and events mark the need for new analyses, exchanges and actions to improve the management of organizations, and consequently the “Dashboard”.In the productive units, the appropriation of the innovation of successive technological revolutions, as well as environmental sustainability, (even more so since Covid-19) are elements of great impact on their transformation and survival.Between the originally proposed Complex Dashboard and the model formulated by Kate Rowarth represented with the “donought economy” at city scale, we detected points of coincidence, which facilitated the reformulation of the original tool as a guide of essential adaptability.Initially, the focus was limited to a local socio-productive and ecological scale to which we incorporated a global view and new dimensions (lenses), which, while making the analysis more complex, also collaborate in meeting the challenges imposed by the 21st century to those who carry out productive activities and want to achieve the highest levels of competitiveness from a socially and environmentally sustainable perspective.
Keywords: meso economy; productive cluster; technological revolutions; environmental sustainability